Multiparametric Analysis of Cerebral Development in Preterm Infants Using Magnetic Resonance Imaging - Dubois, Marine; Legouhy, Antoine; Corouge, Isabelle; Commowick, Olivier; Morel, Baptiste; Pladys, Patrick; Ferré, Jean-Christophe; Barillot, Christian; Proisy, Maïa (Frontiers in Neuroscience, 2021)
Objectives The severity of neurocognitive impairment increases with prematurity. However, its mechanisms remain poorly understood. Our aim was firstly to identify multiparametric magnetic resonance imaging (MRI) markers that differ according to the degree of prematurity, and secondly to evaluate the impact of clinical complications on these markers. Materials and Methods We prospectively enrolled preterm infants who were divided into two groups according to their degree of prematurity: extremely preterm (< 28 weeks’ gestational age) and very preterm (28–32 weeks’ gestational age). They underwent a multiparametric brain MRI scan at term-equivalent age including morphological, diffusion tensor and arterial spin labeling perfusion sequences. We quantified overall and regional volumes, diffusion parameters and cerebral blood flow (CBF). We then compared the parameters for the two groups. We also assessed the effects of clinical data and potential MRI morphological abnormalities on those parameters. Results Thirty-four preterm infants were included. Extremely preterm infants (n=13) had significantly higher frontal relative volumes (p=0.04), frontal GM relative volumes (p=0.03) and regional CBF than very preterm infants, but they had lower brainstem and insular relative volumes (respectively p=0.008 and p=0.04). Preterm infants with WM lesions on MRI had significantly lower overall GM CBF (13.3 ± 2 ml/100g/min versus 17.7 ± 2.5,< ml/100g/min p=0.03). Conclusion MRI brain scans performed at term-equivalent age in preterm infants provide quantitative imaging parameters that differ with respect to the degree of prematurity, related to brain maturation.